The neuroendocrine axis in patients with multiple sclerosis - Wei, T (Brain (London, England : 1878), 1997)
We investigated the basal and dynamic regulation of the hypothalamo-pituitary-adrenal (HPA), hypothalamo-pituitary-thyroid (HPT) and hypothalamo-pituitary-gonadal axes and prolactin secretion in 52 patients with clinically definite multiple sclerosis. These patients also had gadolinium enhanced brain MRI scans and were divided into relapsing-remitting, secondary progressive and primary progressive subgroups. These subgroups were compared with healthy controls and a group of patients with other neurological diseases. The cortisol diurnal rhythm was preserved in all groups of patients. The time-integrated cortisol response to human corticotropin-releasing hormone (CRH) stimulation was lower in the patients with secondary progressive multiple sclerosis, compared with patients with primary progressive multiple sclerosis and healthy subjects. The time-integrated beta-endorphin response to CRH was greater in the patients with relapsing-remitting multiple sclerosis compared with the others. Feedback regulation assessed by dexamethasone suppression was normal. Serum testosterone was low in 24% of male multiple sclerosis patients and oestradiol was low in 25% of pre-menopausal female multiple sclerosis patients, whereas prolactin and the HPT function were normal. Correlations with C-reactive protein (CRP) and MRI suggest that activation of the HPA axis in multiple sclerosis patients is secondary to an active inflammatory stimulus.